PENINGKATAN MINAT DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN SMALL GROUP WORK PADA SISWAKELAS VIII C SMP NEGERI 4 BANGUNTAPAN BANTUL - Sri Lestari (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This research aims to implement small group work learning model to improve students’ interest and achievement in learning Science at the eighth-grade students of SMP Negeri 4 Banguntapan Bantul in the academic year 2013/2014.This research belongs to collaborative Classroom Action Research. The data collecting techniques were done by doing observation, giving questionnaire and test, and making documentation.The results of this research show that the students’ interest in learning Science was improved after small group work learning model had been applied. The percentage of the students’ interest gained from the pre-test was 53,36%, while in cycle I, it was 63,46%, and in cycle II, it was 76,15%. The students’ marks also rose from the mean of their early competence which was 58,65 to 67,69 in cycle I and 76,15 in cycle II. Therefore, it can be said that small group work learning model could improve students’ interest and achievement in learning Science to the eighth-grade students of SMP Negeri 4 Banguntapan Bantul.